Physicochemical evaluation of oil blends of Glycine max L., Helianthus annus L. and Cocos nucifera L. under thermoxidation - Pinheiro, Andressa Alves [UNESP]; Jorge, Neuza [UNESP] (Univ Federal Campina Grande, 2021)
The predominance of mono and polyunsaturated fatty acid of Glycine max L. (soybean) and Helianthus annus L. (sunflower) oils make them more unstable under high temperatures and susceptible to oxidation. On the other hand, the composition of the Cocos nucifera L. (coconut) oil is predominantly saturated and has high oxidative stability. The formulation of oil blends allows some improvements in their nutritional and physicochemical characteristics. Thus, the aim of this work is to evaluate the G. max oil (SB), H. annus oil (SF), C. nucifera oil (C) and the blends G. max: C. nucifera (SB:C, 75:25 v/v) and H. annus:C. nucifera (SF:C, 75:25 v/v) as to their physicochemical properties when under thermoxidation (180 degrees C/15 h). Before the thermoxidation, the C presented less degradation in relation to the others, while the SF:C was the most efficient in inhibiting oxidation due to the presence of low levels of peroxide values, however, it presented less degradation to rho-anisidine and conjugated dieneic acids. The SF:C presented higher oxidative stability and less degradation in relation to SB:C. Consequently, the application of these oil blends is recommendable in processes that involve high temperatures, such as frying.
Keywords: Fatty acids; high temperaturas; oxidation; vegetable oils